Anaemia may add information to standardised disease activity assessment to predict radiographic damage in rheumatoid arthritis: a prospective cohort study. Issue 4 (16th March 2013) - Möller, Burkhard; Scherer, Almut; Förger, Frauke; Villiger, Peter M; Finckh, Axel; ,
Abstract : Objective: Anaemia in rheumatoid arthritis (RA) is prototypical of the chronic disease type and is often neglected in clinical practice. We studied anaemia in relation to disease activity, medications and radiographic progression. Methods: Data were collected between 1996 and 2007 over a mean follow-up of 2.2 years. Anaemia was defined according to WHO (♀ haemoglobin<12 g/dl, ♂: haemoglobin<13 g/dl), or alternative criteria. Anaemia prevalence was studied in relation to disease parameters and pharmacological therapy. Radiographic progression was analysed in 9731 radiograph sets from 2681 patients in crude longitudinal regression models and after adjusting for potential confounding factors, including the clinical disease activity score with the 28-joint count for tender and swollen joints and erythrocyte sedimentation rate (DAS28ESR) or the clinical disease activity index (cDAI), synthetic antirheumatic drugs and antitumour necrosis factor (TNF) therapy. Results: Anaemia prevalence decreased from more than 24% in years before 2001 to 15% in 2007. Erosions progressed significantly faster in patients with anaemia (p<0.001). Adjusted models showed these effects independently of clinical disease activity and other indicators of disease severity. Radiographic damage progression rates were increasing with severity of anaemia, suggesting a 'dose-response effect'. The effect of anaemia on damage progression was maintained in subgroups of patients treated with TNF blockade or corticosteroids, and without non-selective nonsteroidal anti-inflammatory drugs (NSAIDs). Conclusions: Anaemia in RA appears to capture disease processes that remain unmeasured by established disease activity measures in patients with or without TNF blockade, and may help to identify patients with more rapid erosive disease.